Hallux valgus and percutaneous surgery: treatment evaluation - Tavares Cordeiro Neto, Antero; Pereira Neto, Valter; de Schoucair Jambeiro, Jorge Eduardo; Azevedo Alves de Sousa, Lucas; Aguiar de Azevedo, Jones; Delmonte, Fernando; Almeida Matos, Marcos (Journal of the Foot & Ankle, 2022)
Objective: Evaluate the treatment of hallux valgus through percutaneous surgery. Methods: This is a systematic review, and the search was conducted on PubMed/Medline and Virtual Health Library (VHL) databases. The search included studies that addressed percutaneous surgery and analyzed the American Orthopaedic Foot & Ankle Society (AOFAS) score, published between 2013 and 2018, as original studies, in English, Portuguese and Spanish. Results: One-hundred and eighty-five articles were identified in the databases, 19 were selected for STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) application, and five were included in the systematic review. The majority of the studies were European; the age of the patient was from 17 to 78 years, who suffered from mild to severe deformities, which were evaluated radiographically and through the AOFAS scale, then submitted to minimally invasive surgeries. Postoperative follow-up was from six months to ten years. Conclusion: The percutaneous technique for hallux valgus correction has shown good results, little surgical trauma, few complications, rapid recovery, return to activities and high satisfaction with the result. Level of Evidence I; Systematic Review of Level I Studies.